Targeting SRSF10 might inhibit M2 macrophage polarization and potentiate anti‐PD‐1 therapy in hepatocellular carcinoma - Jialiang Cai; Lina Song; Feng Zhang; Suiyi Wu; Guiqi Zhu; Peiling Zhang; Shiping Chen; Junxian Du; Biao Wang; Yufan Cai; Yi Yang; Jinglei Wan; et al. (Cancer Communications)
Abstract Background The efficacy of immune checkpoint blockade therapy in patients with hepatocellular carcinoma (HCC) remains poor. Although serine‐ and arginine‐rich splicing factor (SRSF) family members play crucial roles in tumors, their impact on tumor immunology remains unclear. This study aimed to elucidate the role of SRSF10 in HCC immunotherapy. Methods To identify the key genes associated with immunotherapy resistance, we conducted single‐nuclear RNA sequencing, multiplex immunofluorescence, and The Cancer Genome Atlas and Gene Expression Omnibus database analyses. We investigated the biological functions of SRSF10 in immune evasion using in vitro co‐culture systems, flow cytometry, various tumor‐bearing mouse models, and patient‐derived organotypic tumor spheroids. Results SRSF10 was upregulated in various tumors and associated with poor prognosis. Moreover, SRSF10 positively regulated lactate production, and SRSF10/glycolysis/ histone H3 lysine 18 lactylation (H3K18la) formed a positive feedback loop in tumor cells. Increased lactate levels promoted M2 macrophage polarization, thereby inhibiting CD8+ T cell activity. Mechanistically, SRSF10 interacted with the 3′‐untranslated region of MYB, enhancing MYB RNA stability, and subsequently upregulating key glycolysis‐related enzymes including glucose transporter 1 (GLUT1), hexokinase 1 (HK1), lactate dehydrogenase A (LDHA), resulting in elevated intracellular and extracellular lactate levels. Lactate accumulation induced histone lactylation, which further upregulated SRSF10 expression. Additionally, lactate produced by tumors induced lactylation of the histone H3K18la site upon transport into macrophages, thereby activating transcription and enhancing pro‐tumor macrophage activity. M2 macrophages, in turn, inhibited the enrichment of CD8+ T cells and the proportion of interferon‐γ+CD8+ T cells in the tumor microenvironment (TME), thus creating an immunosuppressive TME. Clinically, SRSF10 could serve as a biomarker for assessing immunotherapy resistance in various solid tumors. Pharmacological targeting of SRSF10 with a selective inhibitor 1C8 enhanced the efficacy of programmed cell death 1 (PD‐1) monoclonal antibodies (mAbs) in both murine and human preclinical models. Conclusions The SRSF10/MYB/glycolysis/lactate axis is critical for triggering immune evasion and anti‐PD‐1 resistance. Inhibiting SRSF10 by 1C8 may overcome anti‐PD‐1 tolerance in HCC.